2019
DOI: 10.1136/bmjopen-2018-025453
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum uric acid and clustering of cardiovascular disease risk factors and renal disorders among Shanghai population: a multicentre and cross-sectional study

Abstract: ObjectivesTo estimate the current prevalence of cardiovascular disease risk factors (CRFs) and renal disorders across serum uric acid (SUA) quartiles, and evaluate the relationships between SUA and CRFs and renal diseases in Shanghai population.Study designObservational, cross-sectional study.SettingData were obtained from the physical check-up of local residents at three hospitals in Shanghai.ParticipantsResidents were invited to take part in a physical check-up and provided informed consent. Exclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 53 publications
2
26
0
3
Order By: Relevance
“…In addition to these studies, Yu et al [21] have reported that SUA can induce oxidative stress and activation of local RAS system leading to senescence and apoptosis, showing a mechanism of uric acidinduced human umbilical vein endothelial dysfunction. Clinical studies have also indicated the relationship between SUA and endothelial dysfunction [22][23][24][25]. As our data showed a weak inverse correlation between SUA and endothelial function, the raised SUA, even in physiological range, may reflect he endothelial dysfunction.…”
Section: Open Access Freely Available Onlinesupporting
confidence: 59%
See 1 more Smart Citation
“…In addition to these studies, Yu et al [21] have reported that SUA can induce oxidative stress and activation of local RAS system leading to senescence and apoptosis, showing a mechanism of uric acidinduced human umbilical vein endothelial dysfunction. Clinical studies have also indicated the relationship between SUA and endothelial dysfunction [22][23][24][25]. As our data showed a weak inverse correlation between SUA and endothelial function, the raised SUA, even in physiological range, may reflect he endothelial dysfunction.…”
Section: Open Access Freely Available Onlinesupporting
confidence: 59%
“…We also add the estimation whether eGFR 60 mL/ min/1.73 m 2 of renal function is related with SUA. Furthermore, experimental and clinical studies have also indicated the relationship between SUA and endothelial dysfunction [21][22][23][24][25]. Therefore, we have studied whether interrelationship among eGFR>60 mL/ min/1.73 m 2 , FMD and SUA are correlated.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Originally, obesity was considered a predisposing risk factor, although nowadays, according to the American Heart Association, it has been upgraded to the principal factor. [7][8][9] The key risk factors are additive, due to their predictive power. Consequently, total risk of CVD is the sum of respective risks arising from the incidence of major CRFs.…”
Section: Introductionmentioning
confidence: 99%
“…Studija Tao i sar. ukazuje da je hiperurikemija specifično udružena sa KV faktorima rizika kod žena (18). Stubnova i sar.…”
Section: Diskusijaunclassified